Dynamic changes in γδT cells and bone resorption markers after zoledronic acid in multiple myeloma: A prospective study - Chao-Hung Wei; Yeu-Chin Chen; Shang-Yi Huang (Journal of the Formosan Medical Association, 2025)
We conducted a prospective evaluation for the dynamic change of γδT cells in peripheral blood (PB) and N-telopeptide of type I collagen in urine (uNTX) of patients diagnosed with multiple myeloma (MM) who underwent their initial treatment with zoledronic acid (ZOA; Zobonic®, TTY, Taiwan). Between March 2012 and November 2015, a total of 35 patients were enrolled, including 25 newly diagnosed MM (NDMM) patients. The percentage of γδT cells in PB was assessed at 20 days prior to the first ZOA infusion, then at day 8, day 64, and day 85 after the infusion. Simultaneously, uNTX levels were measured as well. Thirty-three patients who had received at least one dose of ZOA were included in subsequent analysis. We identified three dynamic change patterns for γδT cells: fluctuated pattern, continuously increasing pattern, and continuously decreasing pattern. Among NDMM patients, those exhibiting a continuously increasing pattern showed a significantly shorter overall survival compared to those with the other two patterns combined (4.7 months vs. 92.9 months, p = 0.037). For uNTX, which levels significantly decreased following ZOA treatment. In conclusion, our findings reveal three distinct dynamic change patterns for γδT cells after ZOA initiation, with continuously increasing pattern being associated with a poor prognosis. These findings prompt further inquiry into the role of γδT cells in MM patients and support the suppressive nature of γδT cells and their associated tumor microenvironment.